2017
DOI: 10.1002/jctb.5341
|View full text |Cite
|
Sign up to set email alerts
|

Performance of thermophilic anaerobic digesters using inoculum mixes with enhanced methanogenic diversity

Abstract: BACKGROUND: Various mixes of seeds have been quasi-randomly selected to startup anaerobic digesters. In contrast, this study examines the impact of inoculating thermophilic anaerobic digesters with a designed mix of non-acclimated seeds based on their methanogen composition, using quantitative polymerase chain reaction (QPCR) of 16S rRNA gene, to achieve high abundance and diversity of methanogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The addition of the four bacterial strains and their mixture to the biogas digesters enhanced the methane yield by 10-11%, but it was not as efficient as the original communities, indicating the significant contribution by the members of the enriched communities present in low abundance. Therefore, mixing inocula from different sources can be selected as another strategy to promote a diverse and robust microbial consortium in TAD with enhanced buffering capacity and lower propionate accumulation [48,98] (Figure 2).…”
Section: Strategies To Enhance the Efficiency Of Tad 61 Development O...mentioning
confidence: 99%
“…The addition of the four bacterial strains and their mixture to the biogas digesters enhanced the methane yield by 10-11%, but it was not as efficient as the original communities, indicating the significant contribution by the members of the enriched communities present in low abundance. Therefore, mixing inocula from different sources can be selected as another strategy to promote a diverse and robust microbial consortium in TAD with enhanced buffering capacity and lower propionate accumulation [48,98] (Figure 2).…”
Section: Strategies To Enhance the Efficiency Of Tad 61 Development O...mentioning
confidence: 99%
“…The development of resilient microbiomes that can be acclimatized under thermophilic temperatures and resist the inhibitory concentrations by adjusting the substrate: inoculum ratio is one of the conventional pretreatments. Ghanimeh et al indicated that by inoculating (digestate, manure, and activated sludge) thermophilic anaerobic digesters during the loading period, the pH decreased to 7.2 and gradually increased to stabilize at 7.8, confirming the acclimation of microbial flora [78]. Elsewhere, the co-digestion of different substrates has also been reported as a conventional pretreatment method, which can be implemented without any major modification in the system.…”
Section: Effect Of Pretreatment Techniques In the Ad Systemmentioning
confidence: 99%